Design and synthesis of a clickable, photoreactive amino acid p-(4-(but-3-yn-1-yl)benzoyl)-l-phenylalanine for peptide photoaffinity labeling. Issue 2 (4th January 2023) - Han, Penggang; Wang, Fuli; Bao, Shaoheng; Yao, Ge; Wan, Xiukun; Liu, JiaJia; Jiang, Hui
Abstract : The clickable and photoreactive amino acid is prepared in 11 steps from 3-(4-bromophenyl)-1-propanol. Abstract : Photoaffinity labeling is a powerful technique to investigate the interactions between bioactive peptides and their targets. To construct a peptide-derived photoaffinity probe, at least two amino acids need to be modified or replaced, increasing experimental difficulties and negatively affecting activity. Herein, we report the synthesis of a clickable, photoreactive amino acid p -(4-(but-3-yn-1-yl)benzoyl)-l -phenylalanine (Abpa) and its Fmoc-protected version from 3-(4-bromophenyl)-1-propanol in 11 steps with an overall 12.5% yield. The amino acid contains both a photoreactive benzophenone and a clickable terminal alkyne which acts like a reporter tag by fast attachment to other functional groups via 'click' reaction, and a photoaffinity probe could be created by one single amino acid substitution during peptide synthesis. And its small size helps to retain bioactivity. The efficiency of Abpa was demonstrated by photoaffinity labeling experiments using photoactivatable probes of α-conotoxin MI.